Upaya Komisi Independen Pemilihan Kota Banda Aceh Dalam Memenuhi Aksesibilitas Bagi Penyandang Disabilitas Pada Pemilihan Umum - Rispalman Rispalman; Mukhlizar Mukhlizar (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Political rights is one of basic human rights include disabled person. Disabled person political rights problem often occur in general election. This was related to accessibility for disabled person to participate in general election. Komisi Independen Pemilihan (KIP) Banda Aceh city is general election organizer which responsible for general election process in Banda Aceh city. this research illustrate Komisi independen pemilihan effort and constraint to fulfil accessibility for disabled person in general election. Field research with empiric law research from human behaviour method used in this study. Generally various attempts to give accessibility for disabled person such as special data collection access for disabled person, socialization about election and voting place for disabled person provided KIP Banda Aceh city. Problem in acess such as difficulty in disabled person data collection still found.